Runaway thinning of the low-elevation Yakutat Glacier, Alaska, and its sensitivity to climate change - Trüssel, Barbara L.; Truffer, Martin; Hock, Regine; Motyka, Roman J.; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Zhang, Jing (Journal of Glaciology, 2015)
ISSN:0022-1430 ISSN:1727-5652